ANALISIS LOKUSI, ILOKUSI, DAN PERLOKUSI PADA IKLAN TEH PUCUK HARUM - Setyorini, Ririn; Sari, Intan Purnama (Kajian Linguistik dan Sastra, 2020)
This article aims to escribe the types of speech acts, such as illocution and to tell the function of perlocusion in the Teh Pucuk Harum commercial. In addition, this article also aims to describe the reaction of the audience of the Teh Pucuk Harum commercial. There are three stages in this research; they are (1) observation stage, which involved ‘simak bebas libat cakap’ method, the ‘cakap’ method, and the ‘catat’ technique. (2) the analyses stage include illocution, locution, ad perlocution. (3) the last stage is to describe the result in an informal way. From the analyses, it is known that in the perlocution acts, there are directive speech act, where the illocution only gives information. Meanwhile, the result gathered from the interview shows that the audience were attracted to the Teh Pucuk Harum commercial because it has the morale value to work together to achieve a good hope. Keyword: Language, speech acts, advertisements, pragmatics